2012
DOI: 10.1016/j.immuni.2012.06.019
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factors Thpok and LRF Are Necessary and Partly Redundant for T Helper Cell Differentiation

Abstract: Summary T helper (Th) cells are critical for defenses against infection and recognize peptides bound to Class II Major Histocompatibility Complex (MHC-II) molecules. Although transcription factors have been identified that direct helper cells into specific effector fates, whether a ‘master’ regulator controls the developmental program common to all Th cells remains unclear. Here we showed that the two transcription factors Thpok and LRF share this function. Although disruption of both factors did not prevent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 64 publications
2
58
0
Order By: Relevance
“…2a). A recent study further demonstrated that Thpok and LRF cooperate to regulate T helper (Th) cell gene expression and function [89]. Thpok is also necessary for the development and function of post-thymic effector Th cells [90] and innate-like T cells such as γδT [91] and invariant natural killer T (iNKT) cells [92].…”
Section: Zbtb Function In Hematopoietic Developmentmentioning
confidence: 99%
“…2a). A recent study further demonstrated that Thpok and LRF cooperate to regulate T helper (Th) cell gene expression and function [89]. Thpok is also necessary for the development and function of post-thymic effector Th cells [90] and innate-like T cells such as γδT [91] and invariant natural killer T (iNKT) cells [92].…”
Section: Zbtb Function In Hematopoietic Developmentmentioning
confidence: 99%
“…31 Further light was shed on these findings when a new and unexpected role for LRF in peripheral T-cell function was recently revealed. 37 Previous reports had suggested that Thpok (T-helper-inducing POZ/Kruppel like factor; also known as ZBTB7B) functions as a master regulator of CD41 T-cells, as in its absence, CD41 CD81 double-positive T-cells preferentially differentiate into CD81 T2 cells in the thymus. 38,39 It was therefore presumed that Thpok was essential not only for CD41 T-cell differentiation but also for T helper (Th) cell functions.…”
Section: Interestingly Lrfmentioning
confidence: 99%
“…38,39 It was therefore presumed that Thpok was essential not only for CD41 T-cell differentiation but also for T helper (Th) cell functions. Carpenter et al 37 demonstrated, however, that Thpok is dispensable for many features of Th cell differentiation and that Lrf promotes Th cell gene expression in Thpok-deficient cells. In this study, analysis of Lrf/Thpok double-knockout T cells revealed that mutant cells fail to express Th cell genes or undergo Th cell differentiation in vivo, suggesting that these 2 transcription factors critically regulate Th cell gene expression in a cooperative fashion (Figure 4).…”
Section: Interestingly Lrfmentioning
confidence: 99%
See 1 more Smart Citation
“…The TCR signal-induced zinc finger and BR-C, Ttk, and Bab (BTB) domain-containing protein family transcription factor Th-inducing POK (ThPOK) is dominantly expressed in CD4 ϩ T cells (13) and is necessary for T helper cell differentiation (14,15). ThPOK binds to the silencers within the CD4 and ThPOK gene loci and inhibits silencer activity (13,16).…”
Section: Tip60mentioning
confidence: 99%